Nanorods de ZnO obtenidos a partir de semillas fabricadas por Spray Pyrolysis y Spray Gel : influencia de los parámetros de depósito en las propiedades morfológicas, estructurales, ópticas y actividad fotocatalítica - Sánchez Rodas, Luis Alberto (2015)
In this thesis work an in-depth study of the effects of the conditions of preparation of the seed layers on the morphology, structure, optical properties and photocatalytic activity of nanorods (NRs) of ZnO, grown from these, by wet chemistry methods was realized. Spray Pyrolysis (SP) and Spray-Gel (SG) techniques were used to deposit ZnO seeds from which the Nanorods grew. In the case of seed layers prepared by SP, a solution of zinc acetate was pyrolytically evaporated on a hot substrate at 350 °C, containing different ethanol/water molar ratios in the range of 0 to 0.92. Seed layers prepared by SG were formed from a methanol- based Sol which was sprayed onto a hot substrate at 130 °C. In both cases, transparent conductive glass substrates SnO2:F (FTO) were used. Additionally, Nanorods were further grown on polyethylene terephthalate (PET), in this case the seeds were deposited using only the Spray-Gel technique. The seeds generated by SP or SG were thermally treated in a growth solution prepared from equal volumes of zinc nitrate and sodium hydroxide, after which, and after washing, the nanorods of ZnO were obtained. The resulting materials were morphologically characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-visible spectroscopy and cathodoluminescence (CL). The morphology and structure of ZnO nanorods films depend on the seed generation process, the seeds generated by SP produce vertically aligned nanorods, where the dimensions of their diameters and their dispersion are related to the ethanol/water ratio in the precursor solution. Scanning electron microscopy images and X-ray diffraction patterns indicate that the nanorods have a wurzite (wz) crystal structure, with their c axis as the preferred direction of growth of the nanorods. The diffractograms also indicate the presence of zinc blende structure domains embedded within the majority wurzite structure with a concentration that is highly dependent on the seed film deposition conditions. This, in turn, affects the optical properties of the nanorods, which shows more stacking defects. SG generated seeds mainly form rings, produced during the drying of ZnO drops, and produce films of textured ZnO nanorods, the nanorods are vertical orientation in the rings and multiple oriented outside of them. Finally, the photocatalytic efficiency of the different films of ZnO NRs synthesized on FTO conductive glass substrates and PET was evaluated in the inactivation of E. coli bacteria in water under UV irradiation.